Barriers and facilitators linked to discharge destination following inpatient rehabilitation after traumatic brain injury in older adults: a qualitative study. Issue 17 (14th August 2022) - Souesme, Guillaume; Voyer, Manon; Gagnon, Éric; Terreau, Paule; Fournier-St-Amand, Geneviève; Lacroix, Nadine; Gravel, Kristina; Vaillant, Marie-Claude; Gagné, Marie-Ève; Ouellet, Marie-Christine
Abstract: Purpose: To identify facilitators and barriers associated with returning home for older adults having received inpatient rehabilitation after traumatic brain injury (TBI). Methods: A qualitative design was used. Five older patients with TBI and four family caregivers were interviewed and six healthcare professionals participated in a focus group. Results: Main facilitators to returning home highlighted by all participants were: (1) Patient's adequate health condition and functional status, (2) Access to health and other services at home, (3) Availability of help from a family caregiver. Conversely, if one of these factors was not met, it represented a barrier. Other facilitators identified were (4) Attachment to one's home, (5) Feeling of commitment toward a loved one, (6) Having the possibility of going through a transitional phase, (7) United front between the patient and the family caregiver towards a return home. Additional barriers to returning home included: (8) Incongruent perspectives, and (9) Unclear knowledge about available health and other services at home. Conclusion: The results of this study could be translated into a practical tool to guide patients, families and professionals in the decision about returning home or exploring an alternative option after inpatient rehabilitation for TBI in older adults. IMPLICATIONS FOR REHABILITATION: When orienting an older patient home or to an alternative living environment after a traumatic brain injury (TBI), the perspective of rehabilitation professionals can differ from that of patients and caregivers. Professionals tend to emphasize security, whereas patients and caregivers' focus on the well-being associated with home and on the importance of being with their loved one. Integrating the views, values and wishes of older patients with TBI and their caregivers will support a shared decision-making approach for orientation after rehabilitation.